Peter Mohyla's Translation of the Imitation of Christ - Charipova, Liudmila V. (The historical journal, 2003)
The article is dedicated to one of the least known early works of Peter Mohyla, Orthodox Metropolitan of Kiev (1633–46). Known as a great church and educational reformer and ‘Westernizer’, he made a major contribution to the cultural development in Ruthenia, then a part of the Polish-Lithuanian Commonwealth, and Muscovy in the seventeenth and eighteenth centuries. The work has survived in a single manuscript copy which could have been made from a printed edition that was suppressed or destroyed soon after its publication. The author has established, for the first time, that the work in question is not an original piece, but a rendition of the fifteenth-century Catholic devotional treatise The Imitation of Christ by Thomas à Kempis into contemporary literary Ukrainian. First-hand evidence is presented to support this claim. Mohyla brought many significant changes to the original text using it as a vehicle to convey his own views formed under the influence of the Catholic Reformation, Jesuit education, and Latin books. Conclusions are drawn about the way he applied Western sources to rid the Orthodox Church from obscurity and self-imposed isolation from the European Christian civilization.